2014
DOI: 10.11648/j.jfns.20140203.14
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Packaged Ice Cream in Gaza City, Palestine

Abstract: Abstract:Ice cream is absolutely one of the most popular and favorite food product for Palestinian children and adults.However, it is one of the most favorable foods for bacterial growth and potential source of food poisoning. The main objective of this work was to determine the bacteriological quality of packaged ice cream sold in Gaza city. One hundred samples of traditional sealed packaged ice cream were collected randomly from 20 different food stores of Gaza city. The samples represented all types of ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
3
3
2
Order By: Relevance
“…This substance is vehicle for transmission of this organism. Salmonella was not found in all samples that it is in agreement with studies in Iran and other countries (25,27,28,31), although the contamination levels of 3.7 to 33% have been reported in some studies (21,29,30).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This substance is vehicle for transmission of this organism. Salmonella was not found in all samples that it is in agreement with studies in Iran and other countries (25,27,28,31), although the contamination levels of 3.7 to 33% have been reported in some studies (21,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…In other surveys, more TBC (51 to 78.8%) than the current study has been reported (25)(26)(27). The Enterobacteriaceae and coliform count in food has been considered as an index of food hygiene.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Under these conditions, injured bacterial cells within ice cream have an opportunity for recovery, which was considered as the main cause of foodborne illness. 14,17 The main microorganism activated under these conditions is Salmonella spp., which causes Salmonellosis. Salmonellosis is the most common foodborne illness and is associated with the major outbreaks from ice cream consumption.…”
Section: Introductionmentioning
confidence: 99%